Construction and Expression of Single Recombinant Peptide Surfactant for EOR Application - CUT NANDA SARI; USMAN USMAN; RIESA KW ROHMAT; LENI HERLINA; KEN SAWITRI SULIANDRI; ONIE KRISTIAWAN; DWIYANTARI DWIYANTARI; TATI KRISTIANTI; SONY SUHANDONO (Microbiology Indonesia, 2017)
Surfactant is generally synthetic chemical, which is effective and reliable. However, the chemicals usually did not degraded easily in the environment and could cause damage to the environment. The other possible alternative to produce surfactant is using genetic engineering in order to produce peptide based surfactant. In this research, peptide surfactant was produced using a gene construct which was created using overlapped polymerase chain reaction method (OE-PCR). PAGE analysis shows that single surfactant peptide construction can be expressed by induction of IPTG 1 mM and after at least twice sonication. This research proves that both two constructions have been successfully expressed by producing peptide in expected size (approximately 15 kDa).